Ring-up-doped fiber for the generation of more than 600 W single-mode narrow-band output at 1018 nm - Palma-Vega, Gonzalo; Walbaum, Till; Heinzig, Matthias; Kuhn, Stefan; Hupel, Christian; Hein, Sigrun; Feldkamp, Gerrit; Sattler, Bettina; Nold, Johannes; Haarlammert, Nicoletta; Schreiber, Thomas; Eberhardt, Ramona; et al. (Optics Letters, 2019)
We present the amplification of a narrow-bandwidth signal at a wavelength of 1018 nm to a power exceeding 600 W with a stable output polarization state. The beam showed an excellent, nearly diffraction-limited beam quality. The high-power output could be realized using an in-house designed and fabricated fiber with a core-cladding diameter ratio of 32/260, ultra-low NA of 0.041, and ring-up doping. A seed source with high amplified spontaneous emission (ASE) suppression was also required, which was realized by a double-pass pre-amplifier with 13 W output power.
CRIS-Team Scopus Importer:2023-04-20